STRATEGI PEMBELAJARAN PAI UNTUK MENINGKATKAN SELF-EFFICACY DAN MOTIVASI BELAJAR SISWA BROKEN HOME DI SMPN 7 KOTA BIMA - Junari, Junari; Ruslan, Ruslan; Nasaruddin, Nasaruddin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
Students who come from disharmonious families often experience psychological disorders that affect their self-confidence and motivation in participating in the learning process, especially in Islamic Religious Education subjects that emphasize character building. This study aims to identify Islamic Religious Education teaching strategies that can increase the self-confidence and enthusiasm for learning of students who come from broken families at SMPN 7 Kota Bima. This research method uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that empathy, integration of spiritual values, and role models from educators have an important role in increasing students' self-confidence and interest in learning. Support from a conducive learning environment and personal guidance from teachers also strengthen student participation in the learning process. This study emphasizes the importance of character-based and spiritual learning strategies in the context of inclusive and humanistic education.